The Determinants of Corporate Dividend Policy in Poland - Rój, Justyna (Ekonomika, 2019)
[full article and abstract in English] The purpose of this research is to examine the factors that determine the dividend policy of non-financial firms listed on the Warsaw Stock Exchange (WSE) in Poland and that of the annually paid dividends. Up to now, many empirical studies related to dividend policy were carried out, showing the differentiation of factors affecting the dividend policy and their interaction. Thus, with this study, it would be possible to give a view on the dividend policy of corporations listed on the WSE for the period from 2008 to 2016. The study covers non-financial companies listed on the WSE in Poland. The Tobit regression is used to identify the impact of factors influencing the companies’ distribution of dividends. The variables that may explain a firm’s dividend decision and that were used in this study are selected based on the theory and available empirical researches and then also determined by data availability. These are profitability, investment opportunities, measures of size, leverage, and liquidity. As a result of this study, the factors that determine the dividend policy of companies were verified in the context of the companies listed on the WSE. Moreover, it indicates which of the existing theories on dividend policy could be applied to the capital markets of Poland. Thus, it provides new insights into the theory of dividend policy.